SOCIAL ASPECTS OF LEADERSHIP AND MANAGEMENT - Албул, Ірина (SWorldJournal, 2024)
The article is devoted to issues of social aspects of leadership and management, which are relevant in the conditions of new management thinking. The difference between the status of a leader and a manager is determined by the specifics of their roles and